The e-book phenomenon: a disruptive technology (Libellarium: journal for research in the field of information and related sciences, 2014)
The emergence of the e-book as a major phenomenon in the publishing industry is of interest, world-wide. The English language market, with Amazon.com as the major player in the market may have dominated attention, but the e-book has implications for many other languages and book markets. The pre-e-book publishing world can be seen as a system in which authors delivered texts to publishers, who evaluated, edited, printed and distributed the published text to bookshops and thence to libraries and individual readers. This process has been going on since Gutenberg’s re-invention of movable type in about 1439 (following its original invention in China in the 9th century, and the use of metallic type in Korea in 1234), in other words, for about the past 550 years. The invention of movable type was an instance of a disruptive technology: eventually putting monastic scribes out of business altogether. Similarly, the e-book has the potential to disrupt the processes for the production, distribution and use of authorial texts, and is already in the process of doing so. First, the phenomenon of self-publishing has emerged as a serious contender to the more formal process; secondly, publishers may derive significant economic benefit from the reduction in printing and distribution costs, as well as the ability to sell directly to the consumer through their own Websites; thirdly, the impact on booksellers may result in a further reduction in the number of independent stores – a decline already in process as a result of online bookselling; fourthly, user demand is resulting in libraries wrestling with the problems of how to manage e-books within their collection development and management processes; and, finally, the behaviour of readers is changing as the devices available for using e-books become more numerous and cheaper. Only someone blessed with absolute certainty in forecasting the future can know exactly how things will change, but there is little doubt that the development of the e-book will bring about substantial changes in the processes of book production, distribution and use – and many of these changes will surprise us.
Keywords: e-books; e-publishing; Sweden; small languages; book markets; reading research